Evaluación de las políticas públicas del VIH/SIDA en Ecuador. - Villa Mocha, Emily Tatiana (My University, 2025)
Introduction: HIV/AIDS prevention in Ecuador has gained relevance in the country's health policies. The national strategy for the prevention and control of HIV/AIDS-STIs (ENVIH) has focused on addressing the epidemic through a comprehensive approach, promoting equity and the inclusion of vulnerable populations. Objective: To evaluate the impact of HIV/AIDS health policies applied in Ecuador through an updated literature review. Methodology: A descriptive, retrospective, cross-sectional study with a mixed paradigm, in which a search was carried out in the updated literature during the months of March and April 2025 in the information search engines Google Scholar, PubMed and Cochrane between 2020 and 2025, in Spanish, English and Portuguese, including review articles and meta-analyses with free full-text features. Results: The evidence supports that HIV preventive policies in Ecuador should prioritize sexual education, equitable access to PrEP and dissemination through digital media. These strategies, effective in reducing risk behaviors by up to 60%, require sustainable health management focused on key populations. Conclusions: Historical HIV/AIDS statistics in Ecuador reveal a steady increase in cases. In this regard, HIV/AIDS prevention policies have demonstrated a positive impact on public health in Ecuador by being cost-effective, generating significant savings in treatment and medical care by incorporating innovative and human rights-centered approaches, improving education and access to services, crucial to combating the epidemic.
Introducción: La prevención del VIH/SIDA en Ecuador ha cobrado relevancia en las políticas sanitarias del país la estrategia nacional de prevención y control del VIH/SIDA-ITS (ENVIH) se ha enfocado en abordar la epidemia mediante un enfoque integral promoviendo la equidad y la inclusión de poblaciones vulnerables. Objetivo: Evaluar el impacto que han tenido las políticas sanitarias en VIH/SIDA aplicadas en Ecuador mediante una revisión actualizada de la literatura. Metodología: Estudio descriptivo, retrospectivo, transversal, con paradigma mixto, en el cual se realizó una búsqueda en la literatura actualizada durante los meses de marzo y abril del 2025 en los motores de búsqueda de información google académico, pubmed y cochrane entre el 2020 y el 2025, en idioma español, inglés y portugués incluyendo artículos de revisión y meta-análisis con características de texto completo gratuito. Resultados: La evidencia respalda que políticas preventivas contra el VIH en Ecuador deben priorizar educación sexual, acceso equitativo a PrEP y difusión por medios digitales. Estas estrategias, eficaces en reducir conductas de riesgo hasta en 60% requieren gestión sanitaria sostenible y focalizada en poblaciones clave. Conclusiones: La estadística histórica del VIH/SIDA en Ecuador revela un aumento constante de casos, en este sentido, las políticas de prevención del VIH/SIDA han evidenciado un impacto positivo dentro de la salud pública del Ecuador al tener una relación costo-efectiva, generando ahorros significativos en tratamiento y atención médica incorporando enfoques innovadores y centrados en derechos humanos, mejorando la educación y el acceso a servicios, cruciales para combatir la epidemia.
Keywords: VIH; PREVENCIÓN PRIMARIA; ECUADOR; POLÍTICA SANITARIA